Inovasi Bahan Ajar IPA Interaktif Berbasis Model Pembelajaran Berbasis Masalah melalui Learning Management System di Sekolah Dasar - Wiwit Sanjaya; Desyandri Desyandri; Yalvema Miaz; Ulfia Rahmi (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to develop science teaching materials integrated with Learning Management System (LMS) based on Problem Based Learning (PBL) in elementary schools. The method used is the 4D development model which includes the Define, Design, Develop, and Disseminate stages. The research subjects were fifth grade students in one of the elementary schools, with data collected through observations, interviews, questionnaires, and learning outcomes tests. Data analysis was done descriptively quantitative and qualitative. The results showed that the teaching materials developed were highly valid, practical, and effective in improving students' science learning outcomes. This study recommends wider use of these teaching materials and further development for various topics and levels of education